#TITLE_ALTERNATIVE# - PRATAMA SUKIRNO PUTRA (NIM : 10209070); Pembimbing : Gunawan Handayani, MSCE, Ph.D, INDRA
Seismic refraction method is one of geophysical method used for near-surface geological structure interpretation. In general, a body wave that had been used in identifying the structure below ground level is the pressure wave (P-wave) because the wave is easily obtained when data retrieval and not difficult in processing the data, simply by determining the first break. Along with increased capacity geophysical methods, the shear wave (S-waves) which is a secondary wave can now be used to characterize the layer and composition below the ground surface. Seismic refraction method by using shear waves is one method of seismic measurements that can be utilized in the fields of geotechnical, in particular the determination of the hard layer to the stake building or bridge. Generalized Recicprocal Method (GRM) is an inversion technique in seismic refraction for mapping near-surface structure from forward and reverse shots travel time. Not like other interpretation method, GRM not smoothing the refract data. Results of seismic data processing using GRM more detail than other interpretation methods.